Delayed Treatment and Adverse Effects of Drug Resistance Tuberculosis Impact on Outcome, Survival and Quality of Life - Linda Soebroto; Reviono Reviono; Yusup Subagio Sutanto; Farih Raharjo; Jatu Aphridasari (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2023)
Background: Global TB Report 2020 states that 78% of tuberculosis patients experience drug resistancy with a global treatment success rate of 57%. Drug resistance tuberculosis (DR TB) patients whom experience side effects such as arthralgia and hyperuricemia with inadequate treatment will affect the treatment result.Methods: Retrospective cohort study to DR TB patients who underwent treatment from January 2015 to August 2020 at RSUD dr. Moewardi Surakarta. Survival analysis using Kaplan Meier method and Cox regression test for the effect of risk factors on the safety and survival of TB RO patients. Quality of life analysis using Mann Whitney test.Results: From 372 patients, delayed treatment factor (OR=2.906; 95% CI=1.890-4.469; P≤0.001) and arthralgia factor (OR=1.775; 95% CI=1.148-2.744; P=0.010) were variables that had a significant effect on recovery of DR TB patients. Delayed treatment and arthralgia have risk (2,906 times and 1.775 times) for non-recovered DR TB patients. Delayed treatment factor with HR=14.772 (95% CI=13.381-16.163), arthralgia with HR=15.170 (95% CI=13.960-16.379), and anemia with HR=15.304 (95% CI=14.074-16.535; P=0.002) affect on the survival of DR TB patients. Anemia affect on the quality of life DR TB patients.Conclusion: Delayed treatment for more than 14 days and arthralgia that is not treated adequately can affect the recovery of DR TB patients. The survival and quality of life of DR TB patients can be increased by monitoring the time of taking medication, monitoring side effects of drugs such as arthralgia, and adequate nutritional intake so that anemia does not occur.